An effort to assess the relation between productivity loss costs and presenteeism at work. Issue 1 (2nd January 2017) - Vänni, Kimmo; Neupane, Subas; Nygård, Clas-Håkan
Abstract : Purpose . This study assesses potential presenteeism costs and the association of these with a company's business figures. Materials and methods . We conducted the questionnaire surveys in alternate years between 2003 and 2007 and linked them to sickness absence register data. Perceived work ability levels were assessed and converted into presenteeism days using the Presenteeism Scale tool. Sickness absence and presenteeism days were converted into monetary figures using median monthly salary information. Results . The share of presenteeism costs was constant at about 1% of annual turnover and about 3.7% of personnel costs. The lowest annual presenteeism cost per employee was EUR 986 and the highest was EUR 1302. The lowest number of presenteeism days per employee in a year was 8.7 days and the highest number was 10.4 days. Estimated losses to a company due to sickness absences and presenteeism ranged from EUR 4.6 million to EUR 5.6 million annually. The potential presenteeism costs to the company and to Finnish society were vast. Conclusions . Presenteeism is a costly problem but more research is needed to reveal the connections between presenteeism and a company's turnover, personnel costs and profit.